The determinants of early breast cancer detection via breast self-examination (BSE) in Denpasar, Bali - Ni Made Ari Febriyanti; Dinar Lubis; Dewa Nyoman Wirawan; Ni Luh Putu Suariyani; Mangku Karmaya (Public Health and Preventive Medicine Archive, 2018)
Background and purpose: Breast cancer is the leading cause of death in females, followed by colorectal cancer. Early detection of breast cancer can be done through breast self-examination (BSE). BSE behaviour is influenced by an individual’s level of knowledge and perceptions of the procedure. This study examines the determinants of BSE behaviour in married women aged 15-49 in six villages in the working area of Puskesmas (public health centre) II in West Denpasar, Bali, Indonesia. Methods: A cross-sectional survey was employed with 180 respondents selected by multistage random sampling. Data were collected using standardised questionnaire carried out from November-December 2016. Multiple poisson regression was used to identify the determinants of the BSE behaviours. Results: The proportion of respondents who performed BSE in the three months prior to interview is 55.6%, and, of these, 50.0% reported performing BSE regularly. Multivariate analysis shows the significant determinants of BSE are: high-school and above (APR=2.03; 95%CI:1.41 to 2.92); having a good knowledge of BSE (APR=1.41; 95%CI:1.09 to 1.82); perceived benefits (APR=2, 24; 95%CI:1.53-3.29); perceived low barrier (APR=1.63; 95%CI: 1.16-2.29); and high self-efficacy (APR=1.50;95%CI:1.16-1.95). Conclusions: Level of education, good knowledge of BSE, perceived benefits, perceived low barriers, and high level of self-efficacy are the significant determinants of BSE practice. These findings suggest that education on BSE should be enhanced, particularly for women with lower levels of education.